Auditor switching for opinion shopping, and subsequnt audit quality and audit fee: Evidence from post-SOX period - CHOI, Jong-Hag (Institutional Knowledge at Singapore Management University, 2014)
Theory suggests that firms engage in opinion shopping to obtain better audit opinions. However, there is scarce evidence on the economic consequences of the opinion shopping behaviors. In this paper, we examine the effect of auditor switches for opinion shopping on audit quality and audit fees. Using 30,333 firm-year observations over the 2004-2012 period in the U.S., we first document evidence that firms switch their auditors in search for better audit opinions. Next, we find that the audit quality of clients that switch auditors for opinion shopping is significantly lower than that of clients that did not switch auditors or switched auditors for other purposes. Further tests reveal that these clients pay significantly higher audit fees to their successive auditors. Consequently, we provide compelling evidence that opinion shopping is detrimental to audit quality and auditor independence.